Genetic Factors Affecting Neuroplasticity - Ziske Maritska; Muhammad Fakhri Altyan; Ardy Oktaviandi; Muhammad Barkah; Amirah Dhia Nabila Sinum; Emelda Emelda; Hawari Martanusa; Rini Nindela; Nita Parisa; Bintang Arroyantri Prananjaya; Puji Rizki Suryani; Eka Febri Zulissetiana (Sriwijaya Journal of Medicine, 2023)
Neuroplasticity pertains to the brain's ability to adjust functions or structure in response to events and is an important factor for skill-learning development as well as functional recovery from a neurological disorder. Numerous factors could influence neuroplasticity processes. This literature review aims to discuss the roles of genetic factors in neuroplasticity. The literature search was conducted using the keywords “neuroplasticity”, genetics”, “genes”, and polymorphism” in search engines like google scholar and PubMed, covering original articles, reviews, and text book both in Bahasa Indonesia and English for the last ten years. Genetic variation including gene polymorphism was responsible for the impact of BDNF, ApoE, and dopamine on the functional neural repair of the brain. Certain processes might directly influence neuroplasticity; others might interfere indirectly through the process. A deeper insight into genetic influence regarding neuroplasticity could lead to a better understanding and potential improvement of treatment.